Determination of Median Lethal (LD50) and Growth Reduction (GR50) Dose of Gamma Irradiation for Induced Mutation in Wheat - Sunanda Chakraborty; Sunita Mahapatra; Anubhab Hooi; Md Nasim Ali; Ramesh Satdive (Brazilian Archives of Biology and Technology, 2023)
Abstract The determination of the optimum dose of radiation through its impacts on the growth attributes of the crop is the prerequisite for successful induced mutation breeding. For evaluating the impact of different doses of gamma radiation on wheat (Triticum aestivum), two wheat varieties DBW 187 and K 1006 were irradiated at six different doses (200, 250, 300, 350, 400 and 450 Gy) using a Cobalt-60 source at Bidhan Chandra Krishi Viswavidyalaya, West Bengal, India. Seed germination, survivability and seedling length of the irradiated seeds were measured at 7 days after sowing in laboratory experiments, while plant height, panicle length, grains per panicle and 1000 seed weight was recorded for field studies. It was observed that seed germination, survivability and seedling length declined with the increase in gamma radiation dose. The germination percentage showed significant differences among treatments (100 to 75%), while the survival percentage exhibited significant differences from 200 to 300 Gy in both the varieties. The LD50 for DBW 187 and K 1006 were found to be 272.71 and 278.61 respectively, while the GR50 values were 316.22 and 346.73 for DBW 187 and K 1006 respectively under laboratory conditions. The GR50 for field observations were 341.19 Gy and 339.70 Gy for DBW 187 and K 1006 respectively. Hence, the gamma radiation dose between 250 Gy and 300 Gy was found optimum to obtain desirable results. The obtained dose could be used to generate highest mutation mediated changes with least lethal effects in the subsequent generations of wheat.